ANALYSIS OF FACTORS INFLUENCING CONSUMER DECISIONS TO PURCHASE PRODUCTS - Alif Fathurrahman Najib; Nurul Istiqomah; Untari Eka Setiawati (MESP–FEB UNS, 2022)
Entertainment is an industry that is in great demand by humans today. The entertainment industry itself has many derivative industries accompanying its development. The toy industry is one of the derivative sectors that have become a commodity that is reasonably considered. This study aims to analyze the factors that can encourage consumers to make purchasing decisions on toy products, especially from Bandai. The analysis was conducted using independent variables in product quality, product image, price perception, income, and age of consumers. The dependent variable used is the purchase decision on Bandai's toys. The samples used in this study are those who bought or did not buy Bandai's toys and live in Surakarta. The study uses analysis methods with logistic regression. The study results show that to get a higher profit, Bandai can strengthen the image of its products. Maintaining the product image can be done with product introductions through exhibitions or advertisements. In this case, introducing the product through the screening of television series and films is more appropriate because the Bandai toys are derived from related entertainment industry products. The screenings will result in an attachment between consumers and toy products made by Bandai and are expected to encourage consumers to make purchasing decisions.